The Influence of Product Quality, Promotion and Brand Image on Consumer Satisfaction - One Seapfry One Seapfry; Rachmat Gunawan; Yulianingsih (MultiTech Publisher, 2023)
Research to determine consumer responses and the influence of product quality, promotion and brand image on consumer satisfaction at The Coffee Legend, both simultaneously and partially. The subjects of this research are consumers who have made purchases, the sample in this research is 100 respondents. This type of research is descriptive and verification. Test the instrument using validity and reliability tests. Data analysis includes multiple regression, determination tests and simultaneous and partial significance tests. The research results show: (1) The average consumer response to consumer satisfaction at The Coffe Legend is the highest product quality, (2) Product quality, promotion and brand image have a positive and significant effect on customer satisfaction partially or simultaneously